Effects of Emotion Dysregulation on Post-treatment Post-traumatic Stress Disorder and Depressive Symptoms Among Women Veterans With Military Sexual Trauma. Issue 15 (August 2022) - Lopez, Cristina M.; Gilmore, Amanda K.; Brown, Wilson J.; Hahn, Christine K.; Muzzy, Wendy; Grubaugh, Anouk; Acierno, Ron
Military sexual trauma (MST), defined as sexual assault or repeated, threatening sexual harassment while in the military, is associated with increased risk of long-term mental and physical health problems, with the most common being symptoms of post-traumatic stress disorder (PTSD) and depression. In addition to PTSD and depression, MST is linked to difficulties in emotion regulation as well as poor treatment engagement. Thus, it is important to examine these correlates, and how they affect postintervention symptom reduction in this vulnerable population. The current study presents secondary data analyses from a randomized clinical trial comparing the efficacy of in-person versus telemedicine delivery of prolonged exposure therapy for female veterans with MST-related PTSD ( n = 151). Results of the study found that changes in difficulties with emotion regulation predicted postintervention depressive symptoms but not postintervention PTSD symptoms. Neither postintervention depressive nor PTSD symptoms were affected by treatment dosing (i.e., number of sessions attended) nor treatment condition (i.e., in-person vs. telemedicine). Findings from the current study provide preliminary evidence that decreases in difficulties with emotion regulation during PTSD treatment are associated with decreases in depressive symptom severity.